2020
DOI: 10.35609/jmmr.2020.5.3(5)
|View full text |Cite
|
Sign up to set email alerts
|

Do Millennials Believe in Food Vlogger Reviews? A Study of Food Vlogs as a Source of Information

Abstract: Objective – Developments in communication technology and social media have enabled business to enter the digital world. This can come in the form of ‘vlogs’ or ‘video blogs’ designed by ‘vloggers’ or ‘video bloggers’ to present interesting content and concepts. Food vlogs provide detailed information or explanations about the food vloggers have tried and evaluated, in an interesting video format that shows how the seller prepares the food and serves it up, and how it is consumed. The completed video is uploade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The results of research by [4] revealed that attitude is a reaction or response from Millennials to food vlogger reviews on YouTube platform, which then prompt the individual behavior to buy. Attitudes are formed when a person evaluates an object or idea as favorable or unfavorable, and then develops emotional feelings and tendencies to take action regarding it [9].…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…The results of research by [4] revealed that attitude is a reaction or response from Millennials to food vlogger reviews on YouTube platform, which then prompt the individual behavior to buy. Attitudes are formed when a person evaluates an object or idea as favorable or unfavorable, and then develops emotional feelings and tendencies to take action regarding it [9].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, the attitudes towards online reviews are the result of evaluating product or service attributes that are identified and felt, and the result is in consumers ultimately making a purchase decision. The results of previous research found that active consumers on social media, who have the same interests, often discuss and share experiences when considering purchasing decisions in relation to traveling solo [10] [11] [12], food vloggers [4], beauty vloggers [3], and information sources in the hospitality industry [13].…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations